Courts and criminal justice in America - Siegel, Larry J. (Pearson, 2018)
Legal foundations -- Who controls the courts -- Federal courts -- State courts -- Juvenile courts -- Specialized courts -- Judges -- Prosecutors -- Defense attorneys -- Defendants and victims : their roles and rights -- Pretrial procedures -- Plea bargaining and guilty pleas -- The jury and the trial -- Sentencing, appeals, and habeas corpus -- Differential treatment and wrongful convictions -- Technology, alternatives, and the future